Strategi Pengelolaan Dana Zakat pada Lembaga Amil Zakat Infaq dan Sadaqah Muhammadiyah dalam Mengentaskan Kemiskinan di Kabupaten Ponorogo - Syamsuri Syamsuri; Meichio Lesmana; Wildan Ainun Mardianto (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2023)
This research aims to find out how the strategy of Amil Zakat, Infak, and Shadaqah Muhammdiyah Ponorogo Institutions in alleviating poverty in Ponorogo Regency. Zakat institution was chosen because it has the advantage under the auspices of one of Indonesia's most prominent Islamic organizations and has a good zakat management system to be the winner of laznas best ZIS collection growth in 2020. The method used is qualitatively descriptive with data collection techniques through interviews, observations, and documentation analyzed using SWOT and triangulate analysis techniques. The results of this study showed the collection conducted by LAZISMU Ponorogo in collecting zakat funds through direct collection methods consisting of direct services, presentations directly to various institutions or companies, and social media. While the strategy of gathering indirectly includes the media of the figures, establishing cooperation, organizing events, websites, and social media. The distribution strategy is done through consumptive distribution by providing monthly groceries. Productive distribution is carried out by providing capital to MSMEs. In measuring poverty rates, researchers used the Head Count Ratio. In 2018 the poverty rate in Ponorogo reached 90,220 people and decreased in 2019, namely 83,970 people or reduced by 0.7%, equivalent to 6,250 people, and showed that zakat funds became one in helping alleviate poverty based on the collection and distribution of zakat funds in LAZISMU Ponorogo increased from 2018 to 2019 by 82.5%.